The Pivotal Significance of Sociocultural Demarcations in Shaping and Upholding the Ethnic Identity of the Deported Meskhetians (Exemplified in the Context of South Georgia) (Journal of Advanced Research in Social Sciences, 2024)
The article delves into an intricate exploration of the function, significance, and intrinsic characteristics defining social, cultural, and ethnic demarcations, pivotal in shaping the self-perception of the deported Meskhetians. Despite the prevailing consensus emphasizing the pivotal role of historical memory, territorial associations, interconnected emotions, and collective trauma in shaping the identity of the deported Meskhetians, empirical studies underscore the substantial role played by social and cultural boundaries. These boundaries stand as equally significant mechanisms, fostering the preservation of the identity of this community vis-à-vis other ethnic or social groups. A consensus prevails regarding the manifestation of these boundaries, often characterized by unique markers, symbolic representations, specific attributes, or momentous events. The existence of such resemblant boundaries exerts a profound influence on the attitudes, interrelations, and mutual understandings between individuals and discrete groups, thereby exerting a substantial impact on self-perception. The empirical foundation supporting precise assertions and deductions emanates from comprehensive field studies carried out among the deported Meskhetians domiciled in South Georgia. The inquiry into the identity quandary of repatriates is approached from diverse angles, employing a spectrum of methodologies such as the micro-history approach, biographical-narrative interviews, in-depth interviews, and life history analysis. A comparative method was instrumental in juxtaposing and analyzing data sourced from distinct target groups, enabling the correlation of discerned disparities with varying experiences and historical recollections. Specifically, 44 participants spanning various ages and diverse life experiences underwent interviews. The amassed information was meticulously sifted through, considering parameters such as the respondent's age, ethnic background, gender, direct or tangential association with memories linked to the deportation episode. The primary trends influencing the trajectory of identity establishment or preservation, as delineated within the empirical data, were methodically extracted and isolated. The scrutiny of the acquired data revealed striking disparities in how interviewees perceive their own ethnic identity. Equally apparent were discrepancies in the local community's attitudes towards them and their interpretation of the interviewees' ethnicity. Notably, confirmation emerged regarding the existence of specific social and cultural boundaries within the internal dynamics of the deported Meskhetian community. Yet, as expected, conspicuous cultural and social distinctions surfaced between the deported Meskhetians and the local population, emphasizing unequivocal separations. The contention is posited that the distinctiveness of these boundaries is shaped by several factors. Specifically, the respondent's stance concerning ethnic heritage within their internal group, the diverse traditions prevalent within the Georgian ethnic group, anticipation of potential risks inherent in the Armenian ethnic group, and the accrued experiences from intergroup relations collectively contribute to this delineation. The overarching outcomes of the research are deliberated within the realm of prevailing theories pertaining to identity. The assertion is made that the pivotal determinants shaping the self-perception of the deported Meskhetians primarily align within the constructivist theory framework.